Cooperation in the jaywalking dilemma of a road public good due to points guidance. (July 2022) - Sun, Qipeng; Liu, Hang; Wang, Yongjie; Li, Qiong; Chen, Wenqiang; Bai, Pengxia; Xue, Chenlei
Abstract: Jaywalking is a dangerous illegal crossing behavior, which is common but difficult to govern. If road is a kind of public goods, jaywalking can be regarded as a completely uncooperative behavior in the game of the public goods. Jaywalking is a relatively broad concept, which includes both the behaviors of pedestrians running a red light at the crosswalks and the behaviors of pedestrians directly crossing the road regardless of the traffic rules outside the crosswalks. At the same time, the traffic signal settings in the road network include both the signal lights at the intersections and the signal lights in the mid-roadways. The jaywalking behavior outside the crosswalks in the mid-roadways may be more common and difficult to govern due to the lack of management. Therefore, this study aims at the governance of jaywalking behaviors outside the crosswalks in the mid-roadways. Clearly, time pressure has a huge impact on crossing decision-making processes of pedestrians, and even causes pedestrians to fall into a jaywalking dilemma. The points decision-making guidance mechanism (PDGM) established by us is proposed based on a crossing decision-making model and a points guidance system in this problem-oriented context, which takes time pressure as an important factor. The points rules that the points guidance system relies on mainly apply the Elo algorithm to realize the automatic update of the points. The decision-making processes of pedestrians crossing the road can be positively influenced by the PDGM, which adopts a multi-factor crossing decision-making model. Since our PDGM is an innovative soft strategy based on the development of future intelligent transportation systems, which has not yet been established, so the introduction of a simulation modeling method is very necessary. In particular, this paper establishes an agent-based model to describe the effects of various aspects of the PGDM, and further verifies its effectiveness and feasibility with quantitative methods. The PDGM is beneficial to reduce jaywalking behaviors of pedestrians and effectively promote cooperation between pedestrians and traffic rules. The establishment of the PDGM has been proved to be feasible and effective, which can significantly promote legal crossing and improve the level of crossing safety without affecting the operating efficiency of vehicles by a simulation modeling method. The PDGM, which achieves a good performance, can be pioneered and applied to induce pedestrians to cross the road cooperatively and legally. What's more, the PDGM has been proved to be effective and has great potential to be applied to more traffic scenarios. In summary, it is conducive to urban traffic road more efficient and safer through the study of the points guidance mechanism for pedestrians.